Processo penal, direito ao protesto e democracia - Alvares, Giane Alvares Ambrósio (2016)
In Brazil, although the right to protest is protected by the expressed rule of freedom of expression of the thought, of assembly and of association (5º article, items IV, XVI and XVIII of the 1988 Constitution), on some ocasions the states uses your punitive power against the protesters, wich are accused of common crimes and National Security Law crimes. Based on doctrinal and jurisprudencial analysis of the brazilian Democratic State components, on constitutional principles that limits and guides the use of the state punitive power, and also on the understanding that the right to protest is a fundamental right and the perception that the protesters are accused of commiting crimes just because they were part of a protest act, the goal of this scientific wok is to consider the relations e tensions between criminal proceedings, the right to protest and democracy. It is argued in this work that on the situation exposed the state punitive power was revealed as a censorship tool against the right to protest, blemishing constitutional principles of criminal proceedings and weakening the requirements of the Democratic State